Significance of the anthropometric factor in young female volleyballers´ physical abilities, technical skills, psychophysiological properties and performance in the game - Stamm, R. (Universität Potsdam, 2007)
Aim The aim of the present study was to examine young female volleyballers` body build, physical abilities, technical skills and psychophysiological properties in relation to their performance at competitions. The sample consisted of 46 female volleyballers aged 13-16 years. 49 basic anthropometric measurements were measured and 65 proportions and body composition characteristics were calculated. 9 physical ability tests, 9 volleyball technical skills tests and 21 psychophysiological tests were carried out. The game performance was recorded by the computer program Game. The program enabled to fix the performance of technical elements in case of each player. The computer program Game calculated the index of proficiency in case of each girl for each element. The first control group consisted of 74 female volleyballers aged 13-15 years with whom reduced anthropometry was provided and 28 games were recorded. The second control group consisted of 586 ordinary schoolgirls aged 13-16 years with whom full anthropometry was provided.